La situación retórica de la destitución - Richards, Edgardo (2018)
In societies that have adopted a republican system of government, sometimes the status quo becomes intolerable for a political faction, and it will challenge the legal order to depose the head of the government. Using Bitzer’s concept “rhetorical situation”, I affirm that it is possible to identify a rhetorical situation of destitution (RSD). RSD is an aggregate of conflictive power relations, expressions and reasonings that arise when plans are formed to overthrow the elected government. I use texts from the play Julius Caesar by William Shakespeare to illustrate it properly. In RSD I identify certain context conditions, an argumentative device, and the discursive strategy in which the opposition’s arguments are framed. In the argumentative device, a line of argument is used to support a predetermined and not negotiable conclusion. I underline the value of evidence as a distinctive feature in the rhetoric of modernity. The study of recent cases, and the discussion in the public sphere of the issues addressed in this article, should provide citizens with the possibility of making a reasoned assessment of the power struggles that arise in Republican politics.